Number 28 (December 1993) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1993)
(December 1993) - Notes on the Habitat Characteristics of the Backwater Darter, Etheostoma zonifera (Hubbs and Cannon). By M.S. Peterson, 7 pp. Minutes, Regional Reports and News Notes.
Keywords: blackwater darter; etheostoma zonifera